ANALISIS KUALITAS PELAYANAN PUBLIK PADA PROSES PEMBUATAN SURAT IZIN MENGEMUDI PADA KENDARAAN RODA DUA (SIM C): public services, SIM C, brokerage services, illegal levies - Wahyudi, Sigit; Sany, Teny Karunia (JAMAK, 2018)
Public service is one of the government's responsibilities to the community. The implementation of public services is basically more than the community which does not only cover the quantity but also the quality of service. Quality services that can be used in various fields of public services, including services for making two-wheeled driving licenses (SIM C). The results of various factors such as measuring regulatory socialization, low employee performance, corruption, collusion, nepotism, overlapping in the bureaucracy, and lack of supervision led to the low quality of public services. Slow service processes, brokerage services, and fraudulent levies are still found. Improved service system for SIM Administration Administrators is needed in various regions of Indonesia. It can be concluded that the quality of public services (SIM C) is still not optimal and must be improved again in order to reflect excellent quality in meeting public needs. Services for brokers and levy levies need to be followed up firmly so as not to damage the quality of public services. The community must participate in helping the government eradicate the practice of brokering and levy fees.